Preferences for cesarean section among pregnant women at a tertiary hospital in Ho Chi Minh City, Vietnam: Influencing factors and implications for prenatal care - Trang Thi Thuy Hoang; Oanh Thi Hoang Trinh; Chau Giang Huynh; Truc Thanh Thai; Quan Minh Pham; Hue Thi Hoang; Dan Trieu Thanh Nguyen; Minh Thien Nguyen; Hang Thi Phan (PLoS ONE, 2025)
The World Health Organization recommends a cesarean section (CS) rate of 10–15%. However, global rates may increase to 29% by 2030, raising concerns about the potential overuse of CS without medical indications and its consequences, and in Vietnam, the CS rate reached 34.4% in 2021. This study aims to evaluate Vietnamese women’s preferences regarding birth modes and analyze influencing factors, particularly non-medical aspects. This study was conducted at Hung Vuong Hospital in Ho Chi Minh City, Vietnam to survey 599 pregnant women over 36 weeks of gestation. Data were collected through questionnaires covering sociodemographic information, obstetric factors, birth experiences, and knowledge of birth modes. Approximately 27.1% of participants preferred CS. Factors associated with a higher preference for CS included multiparous women with previous CS (adjusted Odds Ratio (aOR) = 41.48, 95% Confidence Interval (CI) 17.56–97.99), fear of complication from vaginal birth (aOR = 6.27, 95% CI: 2.24–17.57), safer for the baby (aOR = 5.08, 95% CI: 2.73–9.46), date of birth affect to the family’s life (aOR = 3.48, 95% CI: 1.49–8.13), advice from relatives (aOR = 6.58, 95% CI: 3.24–13.37), recommendation of healthcare provider for CS (aOR = 7.15, 95% CI: 2.49–20.48), exposing negative experience of other women (aOR = 2.66; 95% CI: 1.43–4.98, concern about postpartum sexual activities (aOR = 1.93; 95% CI: 1.04–3.56). In contrast, knowledge of the benefits and drawbacks of mode of birth (aOR = 0.47; 95% CI: 0.26–0.86) and labor companionship expectations (aOR = 0.45; 95% CI: 0.24–0.85) were protective factors, associated with a lower preference for CS. Findings from this study emphasize the need for enhanced prenatal education and counseling in Vietnam to support informed decision-making concerning childbirth, while also emphasizing that clinicians’ recommendations are a powerful driver of women’s preference for cesarean section, highlighting the importance of targeted strategies in clinical practice.